Systems of protection of apple orchards of different ages pests in Crimea - Balykina, E.B.; Cherniy, A.M. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2016)
The analysis of existing apple protection systems in the Crimea from pests, noted the multiple use of pesticides in gardens — from 14 to 16 chemical treatments per season. Over the last decade in terms of intensification of horticulture marked changes in the species composition of herbivores, established the dominant complex of pests. Designed to protect three apple orchards of the system taking into account the growing age of technology and gardens, the dominant species of pests and the mechanism of action of modern pesticides formulation that enables reduce number of treatments in the 1,5—2,0 times.